2010 IEEE International Symposium on Phased Array Systems and Technology 2010
DOI: 10.1109/array.2010.5613362
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative analysis of how phase errors affect the beam quality of phased arrays

Abstract: We report on our work to quantity the effect of phase errors on the forward gain and pointing offset uncertainty of phased array beams using a combination of simulations, from the aperture array simulator OSKAR, and measurements taken with the aperture array telescope 2-PAD. We demonstrate that for small arrays the limit in phase error is 10°, resulting in a 5% beamwidth pointing offset; while for larger arrays the limiting phase error is 25°, resulting in a 5% reduction in array sensitivity. In addition we ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…Most typical research centres around discussing errors related to vehicle attitude, seawater acoustic absorption, and seafloor topography [9][10][11][12]. Another crucial consideration is to inspect for beam errors, including beam spreading, beam pointing, beam asymmetry, and sidelobes coupling, which may be present in ADCPs and DVLs [13][14][15]. Previous studies have demonstrated that the variance in current velocity estimation is primarily attributed to the movement of scatterers within the beam irradiation region.…”
Section: Introductionmentioning
confidence: 99%
“…Most typical research centres around discussing errors related to vehicle attitude, seawater acoustic absorption, and seafloor topography [9][10][11][12]. Another crucial consideration is to inspect for beam errors, including beam spreading, beam pointing, beam asymmetry, and sidelobes coupling, which may be present in ADCPs and DVLs [13][14][15]. Previous studies have demonstrated that the variance in current velocity estimation is primarily attributed to the movement of scatterers within the beam irradiation region.…”
Section: Introductionmentioning
confidence: 99%
“…But there are no discussions on the systematic distortion. Furthermore, there is research indicating that the effect of random errors could be equivalent to the influence of excitation current errors, and the performances of antenna with random current errors are studied [16,17]. However, there is lack of direct relationship of random position error with the antenna performance.…”
Section: Introductionmentioning
confidence: 99%